Coherent financial cycles for G-7 countries: Why extending credit can be an asset - Yves S. Schüler; Paul H. Hiebert; Tuomas A. Peltonen (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
Failing to account for joint dynamics of credit and asset prices can be hazardous for countercyclical macroprudential policy. We show that composite financial cycles, emphasising expansions and contractions common to credit and asset prices, powerfully predict systemic banking crises. Further, the joint consideration yields a more robust view on financial cycle characteristics, reconciling an empirical puzzle concerning cycle properties when using two popular alternative methodologies: frequency decompositions and standard turning point analysis. Using a novel spectral approach, we establish the following facts for G-7 countries (1970Q1-2013Q4): Relative to business cycles, financial cycles differ in amplitude and persistence - albeit with heterogeneity across countries. Average financial cycle length is around 15 years, compared with 9 years (6.7 excluding Japan) for business cycles. Still, country-level business and financial cycles relate occasionally. Across countries, financial cycle synchronisation is strong for most countries; but not for all. In contrast, business cycles relate homogeneously.
Keywords: C54; E32; E44; E58; G01; 330; Financial cycle; Spectral analysis; Macroprudential policy